Representasi Sosiolinguistik Pada Kognisi Wacana Persuasi Kopi (Sociolinguistic Representation in Coffee Persuasion Discourse Cognition) - Rusdhianti Wuryaningrum; Muji Muji; Yoga Yolanda (Indonesian Language Education and Literature, 2023)
This study aims to describe the sociolinguistic representations found in persuasive discourse, their social roles through context studies, and people's perceptions of the integration of scientific facts. The object of this research is the coffee persuasion discourse found in the coffee industry landscape. The results of this study indicate that there is a psychological impact on cognition, health, lifestyle, and taste. Quantitatively, the integration of scientific facts has a significant impact on persuasive perceptions. That is, scientific information that supports coffee consumption has an impact on increasing the persuasive power of coffee discourse. This is expected to give consideration to the use of variations and strategies in building cognition in discourse related to coffee persuasion.Penelitian ini bertujuan untuk mendeskripsikan representasi sosiolinguistik yang terdapat pada wacana persuasif,Â peran sosialnya melalui kajian konteks, danÂ persepsi masyarakat terhadap integrasi fakta saintifik. Objek penelitian ini adalah wacana persuasi kopi yang terdapat pada lanskap industri kopi. Hasil penelitian ini menunjukkan adanya kognisi dampak psikologis, kesehatan, gaya hidup, dan cita rasa. Secara kuantitatif, integrasi fakta saintifik berdampak signifikan terhadap persepsi persuasif. Artinya, informasi saintifik yang mendukung konsumsi kopi berdampak pada peningkatan daya persuasi wacana kopi. Hal ini diharapkan dapat memberi pertimbangan penggunaan variasi dan strategi dalam membangun kognisi dalam wacana yang berkaitan dengan persuasi kopi.